Differences between STAD Learning Model and DI Learning Model on Pencak Silat Learning Outcomes - Agi Ginanjar; Riki Ramadhan; Widan Adib; Fauzan Effendy (Universitas Pendidikan Indonesia, 2021)
This study aimed to determine the effect differences of the Student Teams-Achievement Divisions (STAD) learning model and the Direct Instruction (DI) learning model on Pencak Silat learning outcomes. The research method used was an experimental quantitative approach with an intact-group comparison design. Participants from the population included 44 students (23 boys and 21 girls) aged 14-15 years selected using systematic sampling. Data collection techniques used observation and document analysis. The data analysis technique employed the independent samples t-test. The study results concluded that there were differences in the effects of the DI learning model and the STAD learning model on Pencak Silat learning outcomes. Furthermore, the result showed that the STAD learning model was better than the DI learning model. Thus, the STAD learning model can improve the Pencak Silat learning outcomes of Junior High-school students.